Comb-assisted cavity ring-down spectroscopy for ultra-sensitive traceable measurements of water vapour in ultra-high purity gases. Issue 1 (1st January 2023) - Fasci, E; D'Agostino, V; Khan, M A; Gravina, S; Porzio, G; Gianfrani, L; Castrillo, A
Abstract: We report on the development of a comb-assisted cavity ring-down spectrometer for trace water mole fraction determinations in high purity gases. By tuning the laser light in coincidence with a H2 O absorption line at 1.3946 µ m, we were able to determine sub-ppm relative concentrations of water vapour in N2 with a sub-percent statistical uncertainty. The sensitivity of the spectrometer was carefully assessed, yielding a detection limit of about 2 nmol/mol.